Clinical Risk Factors for Early Seizure Recurrence in Dogs Hospitalized for Seizure Evaluation. (18th February 2018) - Kwiatkowska, M.; Tipold, A.; Huenerfauth, E.; Pomianowski, A.
Abstract : Background: Epileptic seizures are a common cause for neurological evaluations in dogs. Hypothesis/Objectives: To determine the timing, frequency, and risk factors for early seizure recurrence (ESR) among dogs admitted to the hospital for seizure evaluation and to facilitate rapid decision making about whether dogs should be placed in the intensive care unit (ICU) or day ward. Animals: Nine‐hundred twenty‐two dogs referred for seizure investigation; 214 patients were included. Methods: Retrospective study. Medical records between 2000 and 2017 were reviewed to determine risk factors for ESR. Findings were compared among dogs diagnosed with idiopathic epilepsy (IE), structural epilepsy (StE) and reactive seizures (RS), as well as in all selected cases together. Results: Fifty percent of dogs had a seizure while hospitalized. In the group 53.1 and 52.2% in the StE group, whereas in the RS 40.44% had ESR. The average time to ESR was 7 hours. In IE group, abnormal postictal neurological examination with prosencephalon signs predicted ESR. In StE group, a single generalized or focal seizure 72 hours before hospital admission and abnormal neurologic examination predicted ESR. In the RS group, ERS was predicted by long‐term antiepileptic monotheraphy. When all dogs were analyzed together, abnormal neurological examination, the occurrence of cluster seizures, status epilepticus, or combination of them 72 hours before presentation predicted ESR. Conclusions and Clinical Importance: Epileptic seizures recurred in 50% of patients within a mean time of 7 hours. In general, when cluster seizures, status epilepticus or both occurred 72 hours before presentation and neurological examination was abnormal upon presentation, the dog should be placed in ICU for observation.